GPX1 Pro198Leu polymorphism and GSTP1 Ile105Val polymorphisms are not associated with the risk of schizophrenia in the Chinese Han population. Issue 15 (18th October 2017) - Gao, Huijie; Liu, Chao; Song, Sijia; Zhang, Chuanqiang; Ma, Qun; Li, Xiao; Xu, Luo
Abstract : Increasing lines of evidence show that oxidative stress plays a role in the pathophysiological mechanisms of schizophrenia (SCZ). Polymorphic variants of oxidative stress-related candidate genes GPX1 and GST1 can affect the antioxidant activities of their encoded enzymes. Therefore, this study aimed to explore the association between the single nucleotide polymorphisms (SNPs) of GPX1 and GSTP1 and susceptibility to schizophrenia in the Chinese Han population. DNA from 323 healthy controls and 210 schizophrenic patients was genotyped for SNPs rs1050450 in GPX1 and rs1695 in GSTP1 using a predesigned TaqMan SNP genotyping assay. Differences in genetic distributions between cases and controls were compared using the χ 2 -test. No significant differences in allelic or genotypic frequencies of GPX1 rs1050450 or GSTP1 rs1695 were detected between cases and controls ( GPX1 rs1050450: χ 2 =0.370, P =0.831 by genotype, χ 2 =0.377, P =0.539, odds ratio=1.145, 95% confidence interval=0.743–1.766 by allele; GSTP1 rs1695: χ 2 =1.537, P =0.464 by genotype, χ 2 =1.623, P =0.203, odds ratio=0.813, 95% confidence interval=0.592–1.118 by allele). Our results suggest that GPX1 rs1050450 and GSTP1 rs1695 SNPs are unlikely to play a major role in the pathogenesis of schizophrenia in the Chinese Han population. However, these results should be validated by replication in larger and independent samples.